Enhanced AODV Protocol to Secure Routing in MANET with Optimization Techniques - Keerthika, V; N. Malarvizhi, Dr (International Journal of Engineering and Technology, 2018)
Mobile Adhoc Network is the infrastructure less network. Routing in MANET is the process of information or the packets transmission to the destination node from the source. The routing protocol controls the data flow in any network, it will make efficient to reach its destination. Most protocols are vulnerable to attacks in open media communications and wide are distribution. Since we are in need of better routing protocols are needed for an efficient data transmitting to improve the MANET features. In this paper, we proposed enhancedÂ Â  AODV routing protocol using ABC optimization algorithm to provide secure Routing in MANET. The simulations carried out in NS2 are provided to demonstrate the performance using parameter threshold, throughput, packet success rate, computational overhead, routing overhea .Â